2018
DOI: 10.1186/s12885-018-4566-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety profile of drug-eluting beads transarterial chemoembolization by CalliSpheres® beads in Chinese hepatocellular carcinoma patients

Abstract: BackgroundThis study aimed to investigate the efficacy and safety of drug eluting beads transarterial chemoembolization (DEB-TACE) treatment by CalliSpheres® in Chinese patients with hepatocellular carcinoma (HCC) as well as the predicting factors for response.Methods99 patients with HCC were consecutively enrolled in this study. All participants were treated by CalliSpheres® DEB-TACE. Clinical response was evaluated according to modified Response Evaluation Criteria in Solid Tumors (mRECIST) criteria. Common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 32 publications
3
36
0
Order By: Relevance
“…Several clinical studies showed that doxorubicin‐loaded DEB‐TACE resulted in higher local drug concentration and lower rate of systemic toxicity . CalliSpheres® beads (CB) is the first DEB product in China, and has just been introduced into clinical use in the last two years, mostly in patients with hepatocellular carcinoma . However, to the best of our knowledge, the clinical efficacy and safety of CB have not been assessed in patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies showed that doxorubicin‐loaded DEB‐TACE resulted in higher local drug concentration and lower rate of systemic toxicity . CalliSpheres® beads (CB) is the first DEB product in China, and has just been introduced into clinical use in the last two years, mostly in patients with hepatocellular carcinoma . However, to the best of our knowledge, the clinical efficacy and safety of CB have not been assessed in patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…As to factors affecting treatment outcomes by DEB‐TACE, a previous study discloses that a number of nodules >3 and higher BCLC stage is associated with decreased ORR achievements in HCC patients treated by DEB‐TACE with CSM . A study reveals that higher Child‐Pugh stage, raised ECOG stage and larger number of nodules are correlated with worse OS in 154 HCC patients received DEB‐TACE with DcBeads ® .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the beads used in DEB‐TACE, several previous studies applying HepaSphere ® , DcBeads ® , and some other beads have been reported . CalliSpheres ® Microspheres (CSM), which is a type of microbeads made of polyvinyl alcohol hydrogel, is the first DEB product developed in China, and it is able to load some positively charged drugs such as adriamycin, pirarubicin, and epirubicin due to its negatively charged functional groups . A previous study investigating the pharmacokinetics of DEB‐TACE with CSM in rabbit liver has demonstrated that DEB‐TACE with CSM presents well performance in drug loading, drug releasing, and tolerance, whereas DEB‐TACE with CSM has just been used for treating HCC patients in clinical practice within the past 2 years, and limited information about the treatment efficacy of DEB‐TACE with CSM in HCC patients is reported .…”
Section: Introductionmentioning
confidence: 99%
“…At present, available data on the use of DEB in China are limited, despite the approval of the proprietary microsphere beads used in the present study [CalliSpheres (CB); Hengrui Medicine Co.] in 2016. Although previous toxicology and pharmacokinetic studies have demonstrated the impressive biological safety and durability of CB (18,19), few reports have researched their effects in a clinical setting (20,21). The present analysis was performed to address the efficacy, safety and overall survival (OS) benefits of CB in patients with advanced HCC (stage B or C), as defined by the Barcelona Clinic Liver Cancer (BCLC) criteria (22).…”
Section: Efficacy and Safety Of Drug-eluting Beads For Transarterial mentioning
confidence: 99%